Controlled and dependent: Experiences of living on social assistance in Sweden - Marttila, A; Whitehead, M; Canvin, K; Burström, B (2010)
This study explored experiences of people receiving social assistance in 21st-century Sweden, based on 33 in-depth interviews conducted in 2005 and 2006. Two overarching themes emerged from the accounts, encompassing both a material and a psychosocial dimension of living on social assistance. Recipients reported that social assistance was generally sufficient for their basic material needs but allowed for no extras. It was possible to live on social assistance for a short time, but became difficult in the longer term. Perceptions of powerlessness, hopelessness and dependency were common and had the most damaging consequences for the recipients' perceived wellbeing. Some recipients believed that society at large had negative perceptions of people living on social assistance; it was something to be ashamed of but, at the same time, it was the recipients' only possible source of income. Findings of this study are partly similar to previous studies conducted in Sweden, suggesting that improvement in services should take into account the experiences of social assistance recipients. © 2009 The Author(s). Journal compilation © 2009 Blackwell Publishing Ltd and the International Journal of Social Welfare.